1992
DOI: 10.1182/blood.v79.7.1836.1836
|View full text |Cite
|
Sign up to set email alerts
|

In vivo priming of platelet-activating factor-induced eosinophil chemotaxis in allergic asthmatic individuals

Abstract: The cytokines granulocyte-macrophage colony-stimulating factor (GM- CSF), interleukin (IL)-3, and IL-5 are important modulators of eosinophilia and eosinophil function. Eosinophil chemotaxis is known to be particularly sensitive for cytokine priming. In the present study, we compared chemotactic responses of eosinophils derived from peripheral blood of allergic asthmatics to responses of eosinophils from peripheral blood of healthy individuals. Eosinophils from allergic asthmatics exhibited a markedly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…As peripheral blood eosinophils from asthmatics have been shown to be primed [10,34], the level of CD11b expression on blood eosinophils in this subgroup of asthmatics might reflect the preactivation or priming status of these cells. Extrapolating earlier reports, in which CD11b upregulation on eosinophils appeared to be indicative of cell activation [11], we would expect also a negative correlation between sputum eosinophil CD11b expression and airway responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…As peripheral blood eosinophils from asthmatics have been shown to be primed [10,34], the level of CD11b expression on blood eosinophils in this subgroup of asthmatics might reflect the preactivation or priming status of these cells. Extrapolating earlier reports, in which CD11b upregulation on eosinophils appeared to be indicative of cell activation [11], we would expect also a negative correlation between sputum eosinophil CD11b expression and airway responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is worth mentioning in this context, although it is not the focus of this review, that in addition to expression of potential activation markers, preactivation or 'priming' of blood eosinophils as a result of systemic inflammation has been evaluated using functional assays [40,91,92]. Such experiments have shown that blood eosinophils from subjects with allergy or asthma, particularly after antigen challenge, have a greater degree of adhesion or transendothelial migration or greater responsiveness to chemoattractants for chemotaxis or activation of the respiratory burst, whereas blood eosinophils from normal donors can be 'primed' for greater responses by IL-5 family cytokines in vitro [40,[93][94][95][96][97][98][99]. A disadvantage with the functional assays is the need for isolated eosinophils; cell purification requires a larger blood volume and may in itself promote more activation, as discussed above.…”
Section: Icam-1 (Cd54)mentioning
confidence: 99%
“…Ongoing studies continue to provide evidence for this cytokine activation of eosinophils. Although the eosinophil-active growth factor cytokines contribute to the process of eosinophil activation [3,4], these cytokines alone do not elicit all measures of eosinophil activation, such as enhanced expression of Fc receptor for ε-I [5] or CD40 [6], found on eosinophils from allergic subjects. Other cytokines or tissue or extracellular matrix-derived, activating stimuli are likely to be involved as well in augmenting specific functional capabilities of eosinophils [7].…”
Section: Introductionmentioning
confidence: 99%